ChemInform Abstract: Thermal Intramolecular [2 + 2] Cycloaddition: Synthesis of 3‐Azabicyclo[3.1.1]heptanes from Morita—Baylis—Hillman Adduct‐Derived 4, 4‐Diaryl‐1, 3‐dienes. Issue 16 (April 2015) - Kim, Ko Hoon; Lim, Jin Woo; Lee, Junseung; Go, Min Jeong; Kim, Jae Nyoung
Abstract In addition to 3‐azabicyclo[3.1.1]heptanes, bicyclo[3.1.1]heptane, 3‐oxabicyclo[3.1.1]heptane and 3‐azabicyclo[3.2.0]heptane derivatives could also be prepared.